1986
DOI: 10.1177/019459988609400403
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Perilymph Fistulas without Hearing Loss

Abstract: In 1978, I reported on the diagnostic criteria and therapy based on the treatment of 34 cases of perilymph fistula. Of that group, 20 patients had no hearing loss associated with the fistula. Since that time, an additional 30 cases of fistula--15 without hearing loss--have been seen and treated operatively. The 30 significant variables of history and physical findings identified in the first study were statistically reviewed, along with a new finding that seems highly significant. Twenty-three of the 26 new ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 4 publications
0
30
1
Order By: Relevance
“…e.g. Singleton (1984) have noted, surgically verified fistulas are frcqucntly found in the absence of SNHL. A hearing loss >20 d B was prcscnt in 53% o f our PLFS cases.…”
Section: Cochlear Symptomsmentioning
confidence: 98%
“…e.g. Singleton (1984) have noted, surgically verified fistulas are frcqucntly found in the absence of SNHL. A hearing loss >20 d B was prcscnt in 53% o f our PLFS cases.…”
Section: Cochlear Symptomsmentioning
confidence: 98%
“…Nystagmus may be seen on examination. In the literature vertigo and nystagmus are regarded as an indicator of PLF 13,[26][27][28] reported that only 18% of patients could be operated on the basis of this complaint alone. A pure tone audiometric analysis would reveal a sensorineural hearing loss in majority of patients.…”
Section: Perilymph Fistulamentioning
confidence: 99%
“…Further, a mixed hearing loss may also be encountered, as traumatic fistula may be associated with conductive hearing loss from middle ear pathology. Notably, hearing may be entirely normal in a substantial percentage of patients [21]. Electronystagmography (ENG) may or may not show positional or spontaneous nystagmus or caloric asymmetry in perhaps 50% to 75% of patients.…”
Section: Diagnosismentioning
confidence: 99%
“…Friedland and Wackym [20••] summarize the surgical experience at several institutions, which show overall improvement rate in vestibular symptomatology approximating 90%, whereas stabilization of hearing may be achieved in approximately 50% of patients, and improvement of hearing in a substantially lower percentage. No study has confirmed that some fistulas heal less well than others; however, the literature implies that the more severe the trauma, the less chance for spontaneous healing [21,22]. Following surgical intervention, postoperative care is about the same as that described following stapedectomy [14].…”
Section: Managementmentioning
confidence: 99%